Compliance of the provisions of RTI Act, 2009 by NGOs in Bangladesh : a case-study of BRAC - Hasan, Ziaul (BRAC University, 2016)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2014.